Phytic acid modified polycaprolactone electrospun matrix for active nerve regeneration - Ganesh Prasad Awasthi; Arjun Prasad Tiwari; Miyeon Shin; Krishna Prasad Sharma; In Hong Yang; Changho Yu (Results in Chemistry)
Physicochemical modification of biomaterials has enormous potential for enhanced functionality and applications. Phytic acid (PA) is a sustainable, non-toxic, and environmentally friendly material used for surface modification in different applications. However, the impact of PA on the surface of the biomaterial matrix and its response to nerve cells has not been studied as far as we know. In this study, we fabricated PA-embedded polycaprolactone (PCL) nanofibrous scaffolds using the electrospinning method and studied the potentiality of these scaffolds for primary sensory neuron growth and alignment. The nanofiber morphology of the scaffolds was evaluated using field emission electron microscopy (FESEM). The results showed that the fiber orientation and diameter were dependent on the amount of PA in the electrospinning solution. The degree of orientation of the aligned nanofibers was higher than that of their random counterparts in composite scaffolds. The PA-loaded nanofibers were found to have higher compatibility with dorsal root ganglia (DRG) neuron cells than the corresponding fibers without PA. Further, the PA provided guidance for axon growth along the matrix. Overall, the results suggested that embedding PA into the scaffold could be a better approach for enhancing nerve growth and alignment, which is required for nerve regeneration.